Guidance and Counseling Management for Strengthening Student Character amid Digital Disruption in Papua, Indonesia - Christofus Woge; Yulius Mataputun; Ewendi W Mangolo; Diki Kurniawan; Petrus Irianto (SUJANA: Education and Learning Review, 2026)
Character education has become a central priority in Indonesian schools as digital disruption reshapes students' behavior, social interaction, and moral development. Guidance and counseling services occupy a strategic position in this effort, yet studies on how these services are managed to strengthen student character remain concentrated in Java and other accessible regions, leaving Papua's distinctive cultural, geographic, and institutional context comparatively unexamined. This study investigated the management strategies of guidance and counseling services for strengthening student character at SMA Negeri 1 Serui, Yapen Islands Regency, Papua Province, focusing on planning, organizing, implementation, and evaluation. A qualitative case study design was employed, drawing on in-depth interviews, observation, and document analysis involving 15 participants, comprising the principal, the vice principal for student affairs, guidance and counseling teachers, religious education teachers, and students. Findings show that planning is developed collaboratively around students' needs, organization is structured through a grade-based division of responsibility, implementation is realized through religious, disciplinary, and extracurricular activities integrated into daily school life, and evaluation is conducted periodically to refine ongoing programs. Character development proved most effective when guidance and counseling services were embedded within school culture rather than delivered as an isolated program. This study contributes to guidance and counseling management theory and character education literature by showing how habituation-based frameworks operate under conditions of cultural plurality and limited institutional infrastructure in a digitally disrupted Papuan school setting.